Efeito de ações educativas sobre a percepção ambiental de alunos do 4º e do 5º ano do Ensino Fundamental I: o caso dos projetos relacionados ao convênio “Linha Ecológica” financiado pela Itaipu Binacional - Lozovey, Patricia (2024)
The present research aimed to analyze educational actions promoted by the "Ecological Line: Education for Sustainability and Cultural Development of the Territory" agreement in partnership with the Municipal Government of Corbélia, with the expected impact on the educational field of elementary school students enrolled in municipal schools. Considering the importance of projects that consolidate Environmental Education and Sustainability, some questions needed to be elucidated, especially regarding the assimilation of the concepts addressed. For this research, bibliographic references and documentary sources from authors who deal with this theme were used. Additionally, questionnaires were administered regarding the knowledge acquired about cisterns, school gardens, and healthy eating, along with a questionnaire before and after the technical visit to the Transfer Station and the Association for Solid and Organic Materials Collection (ACOMAR). This allowed us to verify whether students' participation in these activities facilitated knowledge assimilation. As a result, it was possible to observe differences in children’s responses before and after visiting the Transfer Station and ACOMAR, which did not occur in the answers provided by students regarding the cisterns present in schools. Regarding the topic of school gardens and healthy eating, it was evident that despite the lack of direct exposure to this learning tool, children demonstrated an understanding of healthy eating.